2020
DOI: 10.1111/lam.13401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diversity analysis of halophiles at two polar saltern systems in Indramayu, West Java, Indonesia

Abstract: Successive microbes in solar salt ponds are essential since it is well correlated with the quality of salt produced. This research aimed to analyse the microbial diversity of the solar salt ponds in Indonesia, which use high‐density polyethylene in the ponds. There are two systems, that is, an integrated open system (In‐system) and a closed system (Tt‐system). The In‐system uses seawater while the Tt‐system uses seawater from the saline artesian well. Results showed that the In‐system had richer microbes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…It was found that three beneficial genera Halobaculum (596 reads), Haloplanus 903 (reads), and Haloarcula (95 reads) (Koecher et al 2009;Oren 2010Oren , 2014aSo et al 2022) were present in higher abundance in CP-Sampang compared to those in CP-Tuban (Figure 8 and Supplementary Table 6). These 3 archaeal genera were also identified in the Indramayu Indonesia solar saltern (Chasanah et al 2020). Their abundant presence in CP-Sampang can be regarded as good indication of salt quality, since these archaea require high MgCl 2 (Hallsworth et al 2007;Shimoshige et al 2013), thereby lowering Mg 2+ contamination as impurties in the salt produced in the salterns.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was found that three beneficial genera Halobaculum (596 reads), Haloplanus 903 (reads), and Haloarcula (95 reads) (Koecher et al 2009;Oren 2010Oren , 2014aSo et al 2022) were present in higher abundance in CP-Sampang compared to those in CP-Tuban (Figure 8 and Supplementary Table 6). These 3 archaeal genera were also identified in the Indramayu Indonesia solar saltern (Chasanah et al 2020). Their abundant presence in CP-Sampang can be regarded as good indication of salt quality, since these archaea require high MgCl 2 (Hallsworth et al 2007;Shimoshige et al 2013), thereby lowering Mg 2+ contamination as impurties in the salt produced in the salterns.…”
Section: Discussionmentioning
confidence: 91%
“…Journal of Biosciences Journal of Biosciences extensively worldwide (Yang et al 2007;Hedi et al 2009;Najjari et al 2015;Naghoni et al 2017;Barreteau et al 2019;Chasanah et al 2020;Mani et al 2020).…”
Section: H a Y At I H A Y At Imentioning
confidence: 99%